Evaluation of forage potential of tropical grasses under different potassium application times - K. S, Nascimento [UNESP]; Loiola Edvan, R.; Rodrigues, A. C.C.; Gomes, N. S.; Barbosa, R. S.; Martins, V.; Junio de Jesus Lacerda, J. (Taylor & Francis, 2021)
The aim of this study was to evaluate growth, biomass production and mineral composition of forage grasses subjected to different times of potassium (K) application. The experiment was carried out in a greenhouse, from May to October 2017, under randomized block design in a factorial scheme with four replications. The factors consisted of three forage grasses (Brachiaria brizantha–Marandú grass, Panicum maximum–Mombaça grass and Urocloa mosambicensi–Corrente grass) and four times of application of K: no potassium (K-0), 100% of potassium at sowing (K-1), 50% of potassium at sowing and 50% at the first application of nitrogen (K-2) and potassium applied fractioned together with the nitrogen fertilization (K-3). The K levels were corrected by applying 0.08 g per pot (40 Kg ha˗1). The nitrogen (N) fertilization was divided into 8 applications in all treatments (200 kg ha˗1 of nitrogen was applied), with the first application carried out 30 days after sowing. The application of K was executed according to each treatment. The evaluated variables were: height, tiller population density (TTPD), leaf blade/stalk ratio (L/S), number of live leaves per tiller (NLL), live material/dead material ratio (LM/DM), total forage biomass (TFB), crude protein (PB), and contents of phosphorus (P), potassium (K) and magnesium (Mg). The data were subjected to analysis of variance and means comparison test by the Tukey’s test, with p < .05 (statistical analysis system SISVAR, version 5.0). No significant interaction was observed between the factors. LM/DM and TFB were significantly affected by the time K-3. The forage grass genotypes differed in growth and production characteristics, regardless of the K application times. Corrente grass had the highest TFB with 20.1 ± 1.5 t ha˗1. The three grasses presented the highest CP contents with time K-1, with 11.88%, 11.62% and 9.9% for Marandú, Mombaça and Corrente grass, respectively. The application time in which potassium is fractioned together with the nitrogen fertilization (K-3) provides greater production of forage biomass and higher mineral contents for the grasses.
Keywords: biomass; Fertilization; forage; fractionation